Analógico vs Digital. Especificidades e complementaridades a partir de uma experiência pessoal - Marco André Da Silva Rosa (2022)
The author has been provided previously with the opportunity of experiencing an analogue dominant and digital dominant methodology both within his education and practice of architecture. These experiences occurred in Portugal and the United Kingdom, two countries with starkly different approaches to architecture. This thesis intends to analyse these two different experiences within design and construction to therefore propose how each can complement one another. To analyse such work, interviews with lead architects associated with the respective experiences will offer a professional and mature perspective to the work. This will be supported with primary sourced interviews with architects from the architecture talk series Café com Esquissos, along with conversations with individuals from the architectural and art community. These primary sourced references will be supported with literature to provide depth and ensure a well-rounded thesis. The study offered an accurate insight into why and how the tools assisted both the author and respective architects in completing each of the design and construction phases of both methodologies. The study proposed each methodology could complement one another. However, this interaction relied upon two circumstances, design difficulty and the skillset of the workforce both within the design and construction phases. Future studies into the actual application of this hybrid methodology would test these proposed theories.